Comparison of Xbox One and Steam Joystick-based Operating System User Interface using KLM- GOMS - Dodick Zulaimi Sudirman; Yaya Heryadi; Harco Leslie Hendric Spits Warnars; Benfano Soewito; Ford Lumban Gaol; Edi Abdurachman (Journal of Games, Game Art, and Gamification, 2020)
Despite having many advances in video game control such as voice or gesture control, most video game console manufacturers still use a joystick as the main control for their console. Currently, the problem with video game manufacturers is that instead of using the joystick as the point of user interface design, they instead used a design from another device such as a computer or tv. The research will compare Xbox One and Steam OS user interface by using KLM-GOMS Model. Based on the calculation it is concluded that the overall Xbox One has a more efficient design compared to Steam.